Treibhaus 4. - Kunstmuseum Düsseldorf (Düsseldorf : Kunstmuseum Düsseldorf, 1986)
Böhmer, Karl ; Ettlinger, Stefan ; Fries, Pia ; Güdemann, Cordula ; Hausmann, Heinz ; Jesdinsky, Bertram ; Jünger, Bernd ; Kastner, Bernd ; Münchhoff, Ulrike ; Müller, Otto ; Mundt, Wilhelm ; Röing, Johan ; Saheb, Oveis ; Scheu, Elke ; Schmidt, Hans-Peter ; Sehler, Stefan ; etc.
Treibhaus 4, Kunstmuseum Düsseldorf, 19. September bis 12. Oktober 1986
boek